Analysis of microscopic bone properties in an osteoporotic sheep model: a combined biomechanics, FE and ToF-SIMS study. Issue 151 (28th February 2019) - Müller, R.; Henss, A.; Kampschulte, M.; Rohnke, M.; Langheinrich, A. C.; Heiss, C.; Janek, J.; Voigt, A.; Wilke, H. J.; Ignatius, A.; Herfurth, J.; El Khassawna, T.; et al.
Abstract : The present study deals with the characterization of bone quality in a sheep model of postmenopausal osteoporosis. Sheep were sham operated ( n = 7), ovariectomized ( n = 6), ovariectomized and treated with deficient diet ( n = 8) or ovariectomized, treated with deficient diet and glucocorticoid injections ( n = 7). The focus of the study is on the microscopic properties at tissue level. Microscopic mechanical properties of osteoporotic bone were evaluated by a combination of biomechanical testing and mathematical modelling. Sample stiffness and strength were determined by compression tests and finite-element analysis of stress states was conducted. From this, an averaged microscopic Young's modulus at tissue level was determined. Trabecular structure as well as mineral and collagen distribution in samples of sheep vertebrae were analysed by micro-computed tomography and time-of-flight secondary ion mass spectrometry. In the osteoporotic sheep model, a disturbed fibril structure in the triple treated group was observed, but bone loss only occurred in form of reduced trabecular number and thickness and cortical decline, while quality of the residual bone was preserved. The preserved bone tissue properties in the osteoporotic sheep model allowed for an estimation of bone strength which behaves similar to the human case.